Debonding Analysis of FRP-Strengthened Concrete Beam in High-Temperature Environment: An Enhanced Understanding on Sustainable Structure - Xiaoning Zhang; Jianwen Hao; Wei Hou; Jiancheng Yao; Yazhuo Wang; Xiaojian Su; Xiangyang Li (Buildings)
FRP (fiber-reinforced composite) is generally regarded as the repair and enhancement material for existing concrete structures in extreme service environments such as high temperatures or fire exposure. In order to reveal the effect of high temperatures (i.e., thermal load) on the interfacial debonding behavior of a FRP-strengthened concrete beam, the novel closed-form analytical model was established and validated while considering the interfacial bond-slip constitutive. Based on the analytical model, solutions to the distributions of interfacial slip, interfacial shear stress, and debonding load were derived. Moreover, the effects of temperature variations and the FRP’s bonded thickness and length on interfacial bond behavior were also evaluated. The results indicated that the increase in temperature variations accelerated the development trends of interfacial slip and shear stress, where the affected range was mainly concentrated in the bonded plate end. The relationship between temperature variations and debonding loads presented a changing linear trend, and a prediction model for the debonding load was also proposed. Meanwhile, the increase in the FRP’s bonded thickness decreased the bond performance and accelerated the degradation trend of the debonding load. However, the increase in FRP’s bonded length improved the bearing capacity of the FRP-strengthened concrete beam. This paper provides meaningful guidelines for the sustainable design and construction of FRP-strengthened concrete structures in high-temperature environments.